Advanced materials for uranium adsorption: a mini review of recent developments - Liu, Dan; Wang, Yiyuan; Zuo, Liangzhou; Guo, Ming; Liu, Shun (Frontiers in Materials, 2025)
Uranium contamination in water and soil poses serious risks to human health and ecosystems. Adsorption is a promising method for uranium removal due to its efficiency and simplicity. This review highlights recent advancements in uranium (VI) adsorption using Metal-Organic Frameworks (MOFs), Covalent Organic Frameworks (COFs), Graphene Oxide (GO), and MXenes. MOFs and COFs offer high adsorption capacities and tunable structures, while GO and MXenes exhibit excellent performance due to their large surface areas and unique chemical properties. However, challenges such as regeneration costs, material stability, and large-scale production remain significant barriers. This review discusses these challenges, compares material advantages and limitations, and outlines future directions to develop efficient adsorbents for radioactive waste management and environmental remediation.